EFEKTIVITAS MODEL PEMBELAJARAN NHT DENGAN MEDIA KOMIK KELSIPAR TERHADAP HASIL BELAJAR IPAS SDN 1 PADURENAN - Hayya, Dwi Aqiella Fadilla; Ardianti, Sekar Dwi; Kironoratri, Lintang (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Learning outcomes are crucial for improving student understanding. However, at SDN 1 Padurenan, the average student achievement in science is relatively low. In addition to these issues, researchers also identified another issue: a lack of varied teaching activities, leading to students feeling lazy and bored. Innovation is essential for improving students' science learning outcomes. One approach is the Numbered Head Together (NHT) learning model, employing a pre-experimental one-group pretest-posttest design, aided by the KELSIPAR (Local Wisdom of Sirup Parijoto) comic. The purpose of this study is (1) to analyze the difference in the average pretest and posttest scores on the NHT learning model with Kelsipar comic media in science learning at SDN 1 Padurenan, (2) to analyze the improvement in science learning outcomes on the material of changes in the state of matter with the NHT learning model for grade 4 of SDN 1 Padurenan with the effectiveness of Kelsipar comic media. 19 grade IV students of SDN 1 Padurenan were used as research samples. This study uses quantitative research using the pre-experimental one group pretest-posttest design method. This research was obtained through observation, interviews, tests, documentation as well as normality testing, Paired Sample T-Test, and N-Gain tests. From the results of the study, an average pretest of 55.10 increased to 89.68. The average posttest score and Sig. (2-tailed) results were 0.000 <0.5. From the N-Gain Score test, it was 77.80 and declared effective. It was concluded that (1) the average pretest and posttest on the NHT learning model with Kelsipar comic media in science learning at SDN 1 Padurenan had differences, and (2) the results of learning science on the material of changes in the state of matter with the NHT learning model for class 4 of SDN 1 Padurenan with the effectiveness of Kelsipar comic media increased. ABSTRAKHasil belajar sangatlah penting untuk meningkatkan pemahaman siswa. Namun, di SDN 1 Padurenan berbeda, dimana rata-rata hasil berlajar IPAS siswa tergolong rendah. Selain dari permasalahan tersebut, peneliti memperoleh permasalahan lain, yaitu pada kegiatan mengajar yang kurang variatif sehingga menyebabkan peserta didik merasa malas belajar dan membosankan. Dalam kegiatan pembelajaran perlu menggunakan inovasi untuk meningkatkan hasil belajar IPAS siswa. Salah satunya yaitu menggunakan model pembelajaran Numbered Head Together (NHT) dengan metode pre-eksperimental one group pretest-posttest design berbantuan media komik KELSIPAR (Kearifan Lokal Sirup Parijoto). Tujuan dari penelitian ini adalah (1) menganalisis perbedaan rata-rata nilai pretest dan posttest pada model pembelajaran NHT dengan media komik kelsipar pada pembelajaran IPAS di SDN 1 Padurenan, (2) menganalisis peningkatan hasil belajar IPAS materi perubahan wujud zat dengan model pembelajaran NHT kelas 4 SDN 1 Padurenan dengan efektivitas media komik kelsipar. Siswa kelas IV SDN 1 Padurenan berjumlah 19 siswa yang digunakan sebagai sampel penelitian. Penelitian ini menggunakan penelitian kuantitatif dengan menggunakan metode pre-eksperimental one group pretest-posttest design. Penelitian ini diperoleh dengan observasi, wawancara, tes, dokumentasi juga dengan pengujian uji normalitas, uji Paired Sample T-Test, dan uji N-Gain. Dari hasil penelitian tersebut telah diperoleh rata-rata pretest sebesar 55,10 meningkat menjadi 89,68. Skor rata-rata posttest dan hasil Sig. (2-tailed) 0,000 < 0,5. Dari uji N-Gain Score sebesar 77,80 dan dinyatakan efektif. Diperoleh kesimpulan bahwa (1) rata-rata pretest dan posttest pada model pembelajaran NHT dengan media komik kelsipar pada pembelajaran IPAS di SDN 1 Padurenahasil memiliki perbedaan, dan (2) hasil belajar IPAS materi perubahan wujud zat dengan model pembelajaran NHT kelas 4 SDN 1 Padurenan dengan efektivitas media komik kelsipar meningkat.